2018
DOI: 10.1017/wsc.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Incorporated Rye and Hairy Vetch Cover Crop Residue on the Persistence of Weed Seeds in the Soil

Abstract: Incorporation of cover crop residue into the soil has been suggested as a means for reducing weed seedbanks. To explore this hypothesis, we buried mesh bags of seeds mixed with sand at 15-cm depth in late fall in plots that had been planted with rye (Secale cerealeL.) or hairy vetch (Vicia villosaRoth.) or left unplanted. Separate bags contained either velvetleaf (Abutilon theophrastiMedik.), giant foxtail (Setaria faberiHerrm.), Powell amaranth (Amaranthus powelliiS. Watson), or common lambsquarters (Chenopod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…With respect to cover crop effects on seed persistence, our results are consistent with several recent studies suggesting that residues with high C:N ratios may increase seed persistence relative to residues with low C:N ratios or bare soil (Hill et al 2016; Mohler et al 2018). We found no evidence that cover crop–mediated changes in fungal pathogens were responsible for the observed increase in persistence of D. sanguinalis , but the mechanism and significance of this effect remains unclear.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…With respect to cover crop effects on seed persistence, our results are consistent with several recent studies suggesting that residues with high C:N ratios may increase seed persistence relative to residues with low C:N ratios or bare soil (Hill et al 2016; Mohler et al 2018). We found no evidence that cover crop–mediated changes in fungal pathogens were responsible for the observed increase in persistence of D. sanguinalis , but the mechanism and significance of this effect remains unclear.…”
Section: Resultssupporting
confidence: 92%
“…Our results are generally consistent with those of several other studies that also evaluated the impact of cereal rye on persistence of various summer annual weeds. Mohler et al (2018) also found that the persistence of A. powellii was unaffected by rye cover crop residue. However, they found that in the grass species S. faberi , seed persistence (in one of two burial studies) was twice as high in the presence of rye compared with a bare-soil treatment.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This same study concluded that although the biomass accumulation of hairy vetch was very climate-dependent, the total biomass accumulation increased due to delayed termination. Therefore, cover crop termination timing is an important management decision for weed suppression when considering the effect of legume biomass accumulation and resulting effects on plant available N. Mohler et al (2018) evaluated the seed fate of two N-sensitive weeds (Chenopodium album and Amaranthus powellii) and two primarily N-insensitive weeds (Setaria faberi and Abutilon theophrasti) and found that hairy vetch reduced the persistence of the N-sensitive weeds by causing fatal germination, but had no effect on persistence of the other weeds.…”
Section: Nitrogen Availabilitymentioning
confidence: 99%
“…In the other systems, seedlings emerging after cover crop incorporation in June were killed by bed preparation for planting the cabbage in July. The release of nitrogen from the legumes may have triggered substantial fatal germination of these nitrate-sensitive Amaranthus species (Mohler et al 2018), and the fresh residue would have promoted attack on seedlings by pathogenic fungi that the cabbage transplants were robust enough to resist (Mohler et al 2012). The cabbage crop itself was cultivated, hand hoed, and then cultivated late (September 1, 2006).…”
Section: Weed Sciencementioning
confidence: 99%